Representasi Maskulinitas di Tahun 1970-1980an dalam Lagu Ebiet G. Ade - Dipa Nugraha (Center of Language and Cultural Studies, 2021)
This study focuses on the representation of masculinity in Ebiet G. Ade’s songs. This is the implementation of gender or masculinity studies on pop culture products. It aims to provide evidence on the variety of masculine representations in pop culture products in the same period of time. This is qualitative research. Content analysis with transcript method is used. Data is taken from Ebiet G. Ade’s 1988 music album 20 Lagu Terpopuler Ebiet G. Ade Vol. 1-10 1977-1987. The result of this study shows that the masculine representation in Ebiet G. Ade’s songs is different from previous research on the masculine representation of Indonesian men in other pop culture products from the same period.